Koli men lifting the palanquin - Mumbai Archive Project Team (Jio Institute, 2024)
Koli men lift the palanquin onto their shoulders and carry it outside the temple premises. Devotees feel a closer connection to the deity when they participate in carrying the palanquin, as it symbolizes the deity's presence among them.